Arsenic and heavy metals health risk assessment through drinking water consumption in the Peshawar District, Pakistan. Issue 3 (2nd April 2016) - Khan, Sardar; Rauf, Rabia; Muhammad, Said; Qasim, Muhammad; Din, Islamud
ABSTRACT: This study aimed to assess the drinking water quality and human potential health risk in Peshawar, which is the most populous district of Khyber Pakhtunkhwa Province, Pakistan. Water was randomly collected throughout Peshawar District (urban = 45 samples and rural = 29 samples). These samples were analyzed for heavy metal (As, Cd, Co, Cu, Cr, Hg, Ni, Pb, and Zn) concentrations using the atomic absorption spectrometer (Perkin Elmer, AAS-PEA-700). Heavy metal concentrations in drinking water revealed the highest pollution index (PI) values—17.80, 11.92, 7.50, and 5.70 for the Pb, Cr, Cd, and Ni, respectively. The contaminations of Cd and Pb were significantly higher ( p < .05) than their maximum allowable limits set by the World Health Organization. Heavy metal contaminations in drinking water were evaluated for health risk assessment: the chronic risk or hazard quotient (HQ) and cancer risk. Results revealed that HQ values were >1 for the Cd and Pb, suggesting that the exposed human beings could be at chronic risk. Therefore, serious measures such as drinking water treatments and contamination controlling policies are needed to avoid the hazardous effects of toxic heavy metals.